2021
DOI: 10.31083/j.jin.2021.01.284
|View full text |Cite
|
Sign up to set email alerts
|

Extrasynaptic δ-subunit containing GABAA receptors

Abstract: γ-Aminobutyric acid type A receptors (GABAARs) are GABA gated heteropentameric chloride channels responsible for the adult brain’s primary inhibition. In specific brain cells, such as in the hippocampus, one of the subtypes of GABAARs, the δ subunit containing GABAARs (δ-GABAARs), is predominantly expressed and located in extrasynaptic or perisynaptic positions. δ-GABAARs mediate a slow constant inhibitory current called tonic inhibition. While δ-GABAARs and tonic inhibition is critical for the excitability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 167 publications
0
13
0
Order By: Relevance
“…A study by Maguire and Mody ( Maguire and Mody, 2008 ) demonstrated that reduced activation of δ-GABA A Rs has a role in postpartum depression, observing that δ-KO mice have increased depression-like behaviors and an implicit failure in normal maternal behaviors. Brexanolone (allopregnanolone), a neurosteroid agonist which preferentially activates δ-GABA A Rs ( Mihalek et al, 1999 ), has shown efficacy in the treatment of postpartum depression, a condition where endogenous neurosteroids are downregulated in humans ( Ragguett et al, 2019 ; Arslan, 2021 ; Azhar and Din, 2021 ). Rising evidence also suggests that brexanolone could be an effective treatment for other types of mood disorders as well ( Arslan, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Maguire and Mody ( Maguire and Mody, 2008 ) demonstrated that reduced activation of δ-GABA A Rs has a role in postpartum depression, observing that δ-KO mice have increased depression-like behaviors and an implicit failure in normal maternal behaviors. Brexanolone (allopregnanolone), a neurosteroid agonist which preferentially activates δ-GABA A Rs ( Mihalek et al, 1999 ), has shown efficacy in the treatment of postpartum depression, a condition where endogenous neurosteroids are downregulated in humans ( Ragguett et al, 2019 ; Arslan, 2021 ; Azhar and Din, 2021 ). Rising evidence also suggests that brexanolone could be an effective treatment for other types of mood disorders as well ( Arslan, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brexanolone (allopregnanolone), a neurosteroid agonist which preferentially activates δ-GABA A Rs ( Mihalek et al, 1999 ), has shown efficacy in the treatment of postpartum depression, a condition where endogenous neurosteroids are downregulated in humans ( Ragguett et al, 2019 ; Arslan, 2021 ; Azhar and Din, 2021 ). Rising evidence also suggests that brexanolone could be an effective treatment for other types of mood disorders as well ( Arslan, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 δ-GABAARs mediate a slow constant inhibitory current called tonic inhibition during health and disease. 47 Therefore, at the current stage, the regulatory functions of GABAAR subunits under different expressions are becoming more and more significant in life activities and diseases.…”
Section: Expression and Function Of Gabaar Subunitsmentioning
confidence: 99%
“…Gamma-aminobutyric acid type A receptor subunit delta (GABRD) is a ligand-gated ion channel-type receptor that has been linked to a wide range of neurological and psychiatric disease-related symptoms as well as the progression of cancer [ 25 ]. Recent research has shed light on the potential functional functions that GABRD played in the development of malignancies.…”
Section: Introductionmentioning
confidence: 99%